Single in the Church: New Ways to Minister with 52% of God's People - Collier-Stone, Kay (Rowman & Littlefield Publishers, 1992)
Explore the concerns, needs, and fears of single adults and how your church may be ignoring them. Discover practical ways churches have opened their ministries, worship, and congregational life to include singles. An eye-opening discovery that a church growth model need not rely on family-oriented programs and structures.